Neurologic Adverse Events Associated with Voriconazole Therapy: Report of Two Pediatric Cases - Sevliya Öcal Demir; Serkan Atici; Gülşen Akkoç; Nurhayat Yakut; Nilay Baş İkizoğlu; Ela Erdem Eralp; Ahmet Soysal; Mustafa Bakir (Case Reports in Infectious Diseases)
Although voriconazole, a triazole antifungal, is a safe drug, treatment with this agent is associated with certain adverse events such as hepatic, neurologic, and visual disturbances. The current report presents two cases, one a 9-year-old boy and the other a 17-year-old girl, who experienced neurologic side effects associated with voriconazole therapy. Our aim is to remind readers of the side effects of voriconazole therapy in order to prevent unnecessary investigations especially for psychological and ophthalmologic problems. The first case was a 9-year-old boy with cystic fibrosis and invasive aspergillosis that developed photophobia, altered color sensation, and fearful visual hallucination. The second case was a 17-year-old girl with cystic fibrosis and allergic bronchopulmonary aspergillosis, and she experienced photophobia, fatigue, impaired concentration, and insomnia, when the dose of voriconazole therapy was increased from 12 mg/kg/day to 16 mg/kg/day. The complaints of the two patients disappeared after discontinuation of voriconazole therapy. Our experience in these patients reminded us of the importance of being aware of the neurologic adverse events associated with voriconazole therapy in establishing early diagnosis and initiating prompt treatment. In addition, although serum voriconazole concentration was not measured in the present cases, therapeutic drug monitoring for voriconazole seems to be critically important in preventing neurologic side effects in pediatric patients.